2020
DOI: 10.1016/j.compbiolchem.2020.107376
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel human USP2 inhibitor and its putative role in treatment of COVID-19 by inhibiting SARS-CoV-2 papain-like (PLpro) protease

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 76 publications
0
32
0
Order By: Relevance
“…MD simulation of 50 ns was performed at 300 K and 1 atm for two fs under the NPT ensemble. Hydrogen and covalent bonds were constrained using the SHAKE algorithm [ 83 ], whereas system temperature was controlled through Langevin dynamics [ 84 ]. The initial structure was used as a reference, and CPPTRAJ [ 85 ] of AMBER was run to generate a root-mean-square deviation (RMSD) plot to check the system MD simulation convergence [ 81 ].…”
Section: Methodsmentioning
confidence: 99%
“…MD simulation of 50 ns was performed at 300 K and 1 atm for two fs under the NPT ensemble. Hydrogen and covalent bonds were constrained using the SHAKE algorithm [ 83 ], whereas system temperature was controlled through Langevin dynamics [ 84 ]. The initial structure was used as a reference, and CPPTRAJ [ 85 ] of AMBER was run to generate a root-mean-square deviation (RMSD) plot to check the system MD simulation convergence [ 81 ].…”
Section: Methodsmentioning
confidence: 99%
“…Representations in the above equations are: ΔG bind = binding energy; - T Δ S = entropic energy; ΔE MM = molecular mechanics potential energy [van der Waals (ΔE vdw ) energy + electrostatic (ΔE elec )]; ΔG sol = solvation free energy [polar solvation energy (ΔE polar ) + non-polar solvation energy (ΔE SASA ). MM/PBSA analysis has been widely used in binding free energy calculations for anti-viral inhibitors [ 32 , [49] , [50] , [51] , [52] , [53] , [54] , [55] ].…”
Section: Methodsmentioning
confidence: 99%
“…From this perspective, further studies using Usp2 KO mice or specific USP2 inhibitors may be useful for the functional validation of the roles of USP2 in vivo. Meanwhile, drug specificity should be taken into consideration, because many chemical inhibitors have unexpected molecular targets [ 159 ]; for example, a recent paper reported that a USP2 blocker also inhibits severe acute respiratory syndrome coronavirus 2 papain-like protease [ 160 ]. Considering that these inhibitors can affect enzymes with similar structures, chemical inhibitors of USP2 could perturb other endogenous proteins.…”
Section: Perspectivesmentioning
confidence: 99%